“rediseño de la estructura de la torre autosoportada de h=71m para que soporte las antenas de radiofrecuencia y microondas existentes, y 06 antenas de microondas futuras ubicada en la estación 0101711_pi_el_alto, piura”. - Silva Muñoz, Williams Orlando (2016)
This project shows the methodology and the standards and specifications necessary for the Assessment and Redesign (reinforcement ) of the structural tower of section square and self -supported of H=71.00m in height, to support additional burdens on existing along its structure , which it is located in the 0101711_PI_EL_ALTO station in El Alto Province and Department of Piura . An assessment of the current state of the tower took place on stage with the existing loads with the data obtained during the visit to the station where the tower is located. Then in the scenario of existing loads more future loads and subsequently performed the analysis of the proposed redesign on stage of existing loads more the loads future. MsTower V6.0 software is used as a tool for calculation and analysis of the project, considering the American code for telecommunication towers TIA-222F (Allowable Stress Design ASD), the specifications of the American Institute of Steel Construction (AISC) and the National Building Regulation (RNE) from Peru. Which they consider the forces produced on the structure are mainly caused by the wind and further that the wind does not occur simultaneously with the earthquake, being wind action which prevails over the action of the earthquake for this type structures. Therefore for our study is not considered the action of earthquake. It was determined that the structure of the tower in its current state with the existing loads should fail resistance of materials according to current standards and codes, and it was also determined that the structure of the tower in its current state with existing loads more future loads, should fail resistance and exceeds the maximum angular displacements according to the rules and codes. It is concluded that the structure needs strengthening and a proposal was made to redesign the tower to support existing and future loads, and thus present no resistance faults in its entirety and not to exceed the limits of maximum angular displacements according standards and codes. Finally the calculation of measures of the new elements of the redesign was conducted, as well as costs and budget for the project .